1992
DOI: 10.1007/bf00115224
|View full text |Cite
|
Sign up to set email alerts
|

A novel ozone sensor for direct eddy flux measurements

Abstract: Asmall, lightweight (1.5 kg) and fast-response ozone sensor for direct eddy flux measurements has been built. The basis for detection is the chemiluminescence of an organic dye adsorbed on dry silica gel in the reaction with ozone. The chemiluminescence is monitored with a cheap and small blue-sensitive photomultiplier. At a flow rate of 100 I min d the ozone sensor has a 90 % response time of significantly better than 0.1 s with a detection limit lower than 50 ppt at SIN = 3. There are no interferences from o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 21 publications
(35 reference statements)
0
54
0
Order By: Relevance
“…Guesten et al (1992) observed a considerable enhancement of the sensor sensitivity by ∼40 % after abrupt changes of the absolute humidity from 0 to 1 %. The τ − 90 response time was estimated to ∼22 s. Although such sudden humidity changes do not occur in the atmosphere (at least not on stationary measurement platforms), this strong H 2 O cross-sensitivity might introduce a significant source of uncertainty at too rare calibration sequences.…”
Section: Recommendations Concerning Calibrationmentioning
confidence: 88%
See 1 more Smart Citation
“…Guesten et al (1992) observed a considerable enhancement of the sensor sensitivity by ∼40 % after abrupt changes of the absolute humidity from 0 to 1 %. The τ − 90 response time was estimated to ∼22 s. Although such sudden humidity changes do not occur in the atmosphere (at least not on stationary measurement platforms), this strong H 2 O cross-sensitivity might introduce a significant source of uncertainty at too rare calibration sequences.…”
Section: Recommendations Concerning Calibrationmentioning
confidence: 88%
“…(2) A device manufactured by the company GFAS is based on the instrument described by Schurath et al (1991) and Guesten et al (1992). It uses Coumarin-47 as dye and was sold until the year ∼2000.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, eddy covariance fluxes of O 3 were measured with a surface chemiluminescence instrument (Table 1) (Güsten et al, 1992;Güsten and Heinrich, 1996), which was mounted on the three-pod mast with its inlet mounted directly next to that of NO and NO 2 .…”
Section: Eddy Covariance Measurementsmentioning
confidence: 99%
“…The fast O 3 sensor is based on the chemiluminescence of O 3 on the surface of an organic dye adsorbed on silica gel powder deposited on a 1 cm diameter aluminum disk (Güsten et al, 1992). The measurement frequency is 10 Hz, which, at the cruising speed of ∼250 m/s, result in a high spatial resolution of merely ∼25 m. However, turbulence within the inlet tube causes mixing of air which degrades the spatial resolution to effectively 30-40 m distance, still ample for our purposes.…”
Section: Ozonementioning
confidence: 99%